Lactobacillus gasseri SF1183 affects intestinal epithelial cell survival and growth. - Blanda Di Luccia (Public Library of Science (PLoS), 2013)
It is now commonly accepted that the intestinal microbiota plays a crucial role in the gut physiology and homeostasis, and that both qualitative and quantitative alterations in the compositions of the gut flora exert profound effects on the host's intestinal cells. In spite of this, the details of the interaction between commensal bacteria and intestinal cells are still largely unknown and only in few cases the molecular mechanisms have been elucidated. Here we analyze the effects of molecules produced and secreted by Lactobacillus gasseri SF1183 on human intestinal HCT116 cells. L. gasseri is a well known species of lactic acid bacteria, commonly associated to the human intestine and SF1183 is a human strain previously isolated from an ileal biopsy of an healthy volunteer. SF1183 produces and secretes, in a growth phase-dependent way, molecule(s) able to drastically interfere with HCT116 cell proliferation. Although several attempts to purify and identify the bioactive molecule(s) have been so far unsuccessful, a partial characterization has indicated that it is smaller than 3 kDa, thermostable and of proteinaceous nature. L. gasseri molecule(s) stimulate a G1-phase arrest of the cell cycle by up-regulation of p21WAF1 rendering cells protected from intrinsic and extrinsic apoptosis. A L. gasseri-mediated reduction of apoptosis and of cell proliferation could be relevant in protecting epithelial barrier integrity and helping in reconstituting tissutal homeostasis.